Development of a powered - decorticator for producing white pepper from black pepper - CHITHRA G; Dr. Santhi Mary Mathew (Guide) (Tavanur 2007 Department of Post-Harvest Technology and Agricultural Processing)
Development of a powered - decorticator for producing white pepper from black pepper
Development of a powered - decorticator for producing white pepper from black pepper